2018
DOI: 10.1017/s0033291718001277
|View full text |Cite
|
Sign up to set email alerts
|

Testing a stepped care model for binge-eating disorder: a two-step randomized controlled trial

Abstract: The findings indicated that a second step of a stepped care approach did not significantly reduce binge-eating symptoms beyond the effects of USH alone. The study provided some evidence for the second step potentially to reduce factors known to maintain binge eating in the long run, such as attachment avoidance and interpersonal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…This result could be explained with the latest research on the attachment system in patients with BED, in which it was observed that low levels of parental care could have triggered greater confusion and uncertainty in adequately responding to the high frequency of unpleasant emotional experiences (Maxwell et al, ). These experiences have thus contributed to the deficient development of their character, a more severe psychopathological symptomatology and greater difficulty in identifying the sensations of hunger and satiety and accurately distinguishing them from other emotions (Tasca et al, ). This confusion could represent the central nucleus of binges, as discussed in a recent review on this topic (Kittel, Brauhardt, & Hilbert, ).…”
Section: Discussionmentioning
confidence: 99%
“…This result could be explained with the latest research on the attachment system in patients with BED, in which it was observed that low levels of parental care could have triggered greater confusion and uncertainty in adequately responding to the high frequency of unpleasant emotional experiences (Maxwell et al, ). These experiences have thus contributed to the deficient development of their character, a more severe psychopathological symptomatology and greater difficulty in identifying the sensations of hunger and satiety and accurately distinguishing them from other emotions (Tasca et al, ). This confusion could represent the central nucleus of binges, as discussed in a recent review on this topic (Kittel, Brauhardt, & Hilbert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, with this model of treatment less than six sessions were needed per patient, obtaining an overall improve of 63%. Another study (Tasca et al, 2018) tested the usefulness of this approach of intervention for the treatment of binge eating disorder. The findings of this study indicated that the low intensity treatment reduced significantly the symptoms of patients and that a more intensive intervention did not reduce the symptoms more than the low intensity treatment.…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…Each GPIP group consisted of five to 11 members led by one of 11 trained therapists. All therapists had prior experience conducting group therapy and were adequately adherent to the GPIP manual (see Tasca et al, 2013Tasca et al, , 2019. Participants provided written informed consent prior to enrolment.…”
Section: Methods Participantsmentioning
confidence: 99%
“…They also completed the following measures at two time-points (i.e., pre-and 6 months post-treatment): the AAI which was coded with the DMRS, the IIP-64, and the EDE to assess days binged in the past 28 days. Hence, the present study included (a) a re-analysis of previously published outcome data on interpersonal functioning and binge-eating frequency (Tasca et al, 2013(Tasca et al, , 2019, and (b) new data on defensive functioning coded by the DMRS from the AAI audio recordings. We only included pretreatment defensive functioning in this study, as it was the most representative of the potential impact of defensive functioning as it operated early in the therapy groups.…”
Section: Methodsmentioning
confidence: 99%